Leadership Styles and the Sustainability of Community Empowerment Initiatives for Educational Advancement in a Learning Center: A Systematic Literature - Aznem, Ahmad; Warman, Warman (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Effective leadership plays a crucial role in determining the sustainability of community empowerment initiatives in educational advancement, yet the relationship between leadership styles and long-term program sustainability in learning centers remains underexplored. This systematic literature review aims to examine the relationship between leadership styles and sustainability of community empowerment initiatives for educational advancement in learning centers, identify contributing factors to program sustainability, and analyze how contextual characteristics moderate leadership effectiveness. Following PRISMA 2020 guidelines, this review analyzed 24 studies published between 2008-2025 retrieved from Scopus database. Articles were systematically screened using predetermined inclusion criteria focusing on leadership styles, community empowerment, and educational contexts. Data extraction covered bibliographic information, methodological characteristics, contextual factors, and key findings. Thematic analysis was conducted to synthesize findings across studies. Transformational leadership emerged as the most effective style for promoting sustainable community empowerment, demonstrated through enhanced vision creation, stakeholder engagement, and distributed leadership practices. Authentic leadership development programs showed significant impact on breaking barriers and creating sustainable empowerment opportunities. Key sustainability factors include gender-inclusive approaches, community coalition building, empowering supervision mechanisms, and systematic quality management. Contextual moderators such as cultural background, institutional size, resource availability, and program orientation significantly influence leadership effectiveness. Technology-mediated leadership approaches show promise for extending reach and impact of empowerment initiatives. Sustainable community empowerment requires integrated leadership models combining transformational, authentic, and distributed approaches with systematic attention to contextual factors. Success depends on both individual leadership capabilities and supportive organizational systems that facilitate collaboration, inclusion, and quality management. Future research should prioritize longitudinal studies, cross-cultural comparisons, and technology-mediated leadership development.